Improve employee-organization relationships and workplace performance through CSR: Evidence from China - Zhang, Yafei; Dong, Chuqing (Frontiers in Psychology, 2022)
Although CSR research in China has received increasing research attention, employee-centered CSR is still an understudied topic. To fill the void, the purpose of this study is to demonstrate the effects of employees’ CSR perceptions on the quality of employee-organization relationships and workplace performance, as well as the underlying mechanisms explaining such effects, in the Chinese context. Guided by both managerial and relational approaches of corporate social responsibility (CSR) research, we conducted a survey (N = 248) with employees from a large private company in the electric and energy industry in China. Data were analyzed via path analysis using R packages (e.g., lavaan) and results revealed that CSR perceptions can lead to positive employee-organization relationship quality and increase employees’ extra-role performance. We also found that these effects can be further explained by increased employee-organization identification or perceived corporate ability. In addition, a qualitative analysis of employees’ responses showed that the influence of government and Confucianism was reflected in employees’ expectations for their employer’s CSR initiatives. This study contributes to the scant research on employee outcomes and the underlying mechanisms in employee-centered CSR in China. Practically, we add empirical evidence addressing the value of internal CSR for professionals and educators.